Delayed tensile instabilities of hydrogels - Ma, Jie; Yin, Daochen; Sheng, Zhi; Cheng, Jian; Jia, Zheng; Li, Teng; Qu, Shaoxing (Journal of the mechanics and physics of solids, 2022)
Soft materials can undergo various deformation instabilities, including wrinkling, creasing, and necking. Most existing studies of such instabilities of soft materials consider instant instability, which occurs instantaneously when the applied load exceeds a threshold level. Herein, we uncover the delayed tensile instability of hydrogels, a largely unstudied instability mode for soft materials. As the name suggests, when subject to a certain level of tensile load, a hydrogel may remain stable initially, and then suddenly become unstable after a delay in time. We find the delayed instability mode of hydrogels of various shapes, including the necking of stretched double-network hydrogel bars, the burst of pressurized spherical balloons, and the bulging of inflated cylindrical tubes. We reveal that tension-induced water absorption of hydrogels is the key mechanism underpinning the delayed tensile instabilities. The results from this study shed light on new guidelines in designing hydrogels to mitigate or harness deformation instabilities.